T. S. ELIOT’S THE WASTE LAND THROUGH POSTMODERN LENS - Anwar, Md Nurul; Ahad, Md Nurul (Universitas Islam Sumatera Utara (UISU), 2025)
Conventional readings T.S. Eliot’s The Waste Land interpreted it as a poem of utter cultural degeneration, spiritual collapse and mental disillusionment. Its dialectical mode of exchange and opposition between the past and the present invokes complicity to Hegelian dialectical approach that blends thesis (tradition), antithesis (disillusionment) — leading to an anticipation of a final synthesis as a ground of stability in truth and reality. However, the narrative structure of the poem remains resistant to any final synthesis, since the promise of the anticipated renewal does not materialize in any form of final resolution —a state that draws on the postmodern aporia of postponement of meaning supported by Derrida’s Deconstruction. This study thus contends that Eliot’s objective correlative and polyphonic voices support what Adorno (1973) calls “determinate negation of opposites”, thus framing a cultural decline of the present into self-awareness as opposed to the fragmented history of the past. By analyzing unresolved tensions within the poem, the study demonstrates how it enacts différance, positioning Eliot at a critical cusp of the postmodern epistemological departure.